Clinical features and outcomes in patients with pulmonary complications during pregnancy and peripartum. (2nd April 2020) - Han, Yeji; Lee, Jin Hwa; Chang, Jung Hyun; Shim, Sung Shine; Kim, Yookyung; Ryu, Yon Ju
Abstract: Introduction: The aim of this study was to investigate clinical features and identify maternal factors contributing to prognosis in women with pulmonary complications during pregnancy and the peripartum period. Materials and methods: Following a retrospective review of clinical data and radiographic findings between January 2006 and January 2016, 126 women diagnosed with pulmonary complications during pregnancy ( N  = 79) and peripartum within the first 4 weeks after delivery ( N  = 47) were enrolled in this study. Results: Of the 126 patients, 113 (89.7%) required hospitalization. The median age was 32 years, and the percentage of primiparous women was 49.2%. The most common respiratory complaint was dyspnea, followed by cough and fever. Pneumonia developed in 50 patients (39.6%), pulmonary edema in 31 (24.6%), pleural effusion in 28 (22.2%), active pulmonary tuberculosis in 13 (10.3%), and asthma exacerbation in 4 (3.1%). Among the 79 antenatal patients with pulmonary complications, 31 (39.2%) experienced pregnancy-related complications, 21 (26.6%) had an emergency C-section, and 29 (36.7%) had an adverse fetal outcome. Eleven patients (8.7%) developed acute respiratory failure requiring mechanical ventilation, and the overall mortality was 1.6% (2/126) with no pulmonary complication-related deaths. Multiple regression analysis revealed that presence of pregnancy-related complications and younger fetal gestational age at the diagnosis were independent predictive factors for adverse fetal outcomes. Discussion: Pulmonary complications during pregnancy and the peripartum period resulted in poor outcomes, and the risk of adverse fetal outcomes was high, particularly in patients with pregnancy-related complications and younger gestational age at the diagnosis.